Effect of dietary conjugated linoleic acid isomers on water and glycerol permeability of kidney membranes - Soveral, Graca (2015)
Conjugated linoleic acid (CLA) refers to a group of positional and geometrical isomers of linoleic acid in which the double bonds are conjugated. Dietary CLA has been associated with various health benefits although details of its molecular mode of action remain elusive. The effect of CLA supplemented to palm oil-based diets in Wistar Fats, as a mixture of both or isolated c9,t11 and t11,c12 isomers, was examined on water and glycerol membrane permeability of kidney proximal tubule. Although water permeability was unaltered, an increase in glycerol permeability was obtained for the group supplemented with CLA mixture, even though the activation energy for glycerol permeation remained high. This effect was correlated with an increased CLA isomeric membrane incorporation for the same dietary group. These results suggest that diet supplementation with CLA mixture, in contrast to its individual isomers, may enhance membrane fluidity subsequently raising kidney glycerol reabsorption. (C) 2009 Elsevier Inc. All rights reserved.. - FCT [POCT1/CVT/2002/44750, PTDC/CVT/2006/66114, SFRH/BD/2005/22566, SFRH/BPD/2005/23931]. - This study was supported by FCT Grants POCT1/CVT/2002/44750 and PTDC/CVT/2006/66114 and individual FCT fellowships to Susana Martins (SFRH/BD/2005/22566) and Paula Alexandra Lopes (SFRH/BPD/2005/23931). The authors acknowledge Ana Madeira for technical support. We also thank Susana Alves and Rui Bessa (Unidade de Proclucao Animal, L-INIA-REQUIMTE) for providing fatty acid profile analyses.